New currents in western Buddhism The inner meaning of the friends of the western Buddhist order - Sangharakshita (b, 2010)
In this informal manifesto, Sangharashita explains why he founded a new Buddhist movement and examines its relationship to the wider Buddhist tradition.
Keywords: Buddhism. Western world -- Buddhism